Sugar provisioning for ants enhances biological control of mealybugs in citrus - Pérez-Rodríguez, Jésica; Pekas, Apostolos; Tena, Alejandro; Wackers, Felix L. (Elsevier, 2021)
In many agroecosystems, the implementation of an integrated pest management (IPM) program against mealybugs (Hemiptera: Pseudococcidae) is undermined by the presence of ants (Hymenoptera: Formicidae). In a mutualistic association, ants obtain carbohydrates from the mealybugs in the form of honeydew and, in exchange, protect the mealybugs against their natural enemies. Ants however also need protein in their diet. Thus, they can also prey on the mealybugs especially when their carbohydrates requirements are met. This study aims to assess whether providing ants with sugar-feeders (representing ad libitum sources of carbohydrates) I) alters their mutualistic relationships with the mealybugs (ant-tending), II) increases the parasitism of mealybugs, III) increases ant predation rate and IV) alters the protein and carbohydrate profile in ant workers. For this study, we selected a citrus orchard with high infestation levels of the mealybug Planoccocus citri tended by the ant Lasius grandis. Our results showed that sugar provisioning reduced ant activity and ant tending, resulting in an increase of mealybug parasitism rates. Ants showed a tendency to prey more sentinel preys in trees with sugar-feeders, even though the differences were not significant. The gut content in terms of carbohydrates and proteins of ant workers did not differ among trees with and without sugar-feeders. Overall, our results show that sugar provisioning can be used for improving pest management strategies against mealybugs; while further research is necessary to corroborate that predation by ants of honeydew producers increases when sugar-feeders are provided.